THE EFFECT OF OXIDATION ON SAGO STARCH AND ITS APPLICATION AS EDIBLE FILM - Dewi Sondari; Evi Triwulandari; Muhammad Ghozali; Yulianti Sampora; Imad Iltizam; Nanang Masruchin (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2018)
THE EFFECT OF OXIDATION ON SAGO STARCH AND ITS APPLICATION AS EDIBLE FILM. The oxidation reaction with hydrogen peroxide in sago starch can influence the proximate test value, physicochemical properties and edible film properties. The hydrogen peroxide formula for starch modifica- tion is 1, 2, 3 and 4%. The presence of hydrogen peroxide increases the physicochemical properties of sago starch so that the quality of modified sago starch is better than pure sago starch. Glycerol is used to improve film flexibility in the manufacture of edible coatings. The characterization of edible film includes water content, contact angle and elongation. Edible film from modified sago starch shows lower water content compared to pure sago starch films. The oxidation effect of H2O2 on edible film results in changes in the hydrophilic properties including the contact angle. Edible film of pure sago starch shows a lower contact angle value. The hydrophilic nature of edible film decreases in the presence of hydrogen peroxide. The high hydrophobicity of the modified sago starch film is caused by the role of carboxyl groups in the starch molecule chain.